Gelatin methacryloyl/nanosilicate nanocomposite hydrogels encapsulating dexamethasone with a tunable crosslinking density for bone repair - ALARÇİN, EMİNE (My University, 2022)
Despite various strategies have been proposed to accelerate bone regeneration, the treatment of bone defects in critical size still remains a clinical challenge. In this study, we fabricated nanocomposite gelatin methacryloyl (GelMA)/nanosilicate (NS) hydrogels for the delivery of dexamethasone (DEX), and systematically investigated their performance in drug delivery for bone repair. Nanocomposite hydrogels were fabricated by mold casting, and exposed to ultraviolet (UV) light to induce covalent crosslinking. Afterwards, we conducted a systematic characterization study to determine the effects of varying NS concentration, GelMA methacrylation degree and UV exposure time on mechanical, structural, and drug release behaviors of nanocomposite hydrogels. In particular, the higher methacrylation degree of GelMA, longer UV exposure and the presence of NS exhibited gradually enhanced mechanical properties. For instance, the compressive strengths of nanocomposite hydrogels containing 0% (w/v) NS (G0NS120) and 3% (w/v) NS (G3NS120) at 120 s of UV exposure were 194.816 kPa-367.284 kPa (p < 0.001), respectively. Similarly, they exhibited higher swelling ratio (%) and slower degradation rate (%) with longer UV exposure and increased NS amount. Nanocomposite hydrogels revealed slower drug release rate due to longer UV exposure and increased NS amount. At day 14 of the release study, 99.53% and 60.687% of DEX were released from G0NS120 and G3NS120, respectively. Particularly, the nano -composite GelMA/NS hydrogels supported osteoblast adhesion well, and NS and DEX exhibited synergistic effect on osteoblast proliferation with 5.01 fold increase after 7 days of culture. Our results clearly showed that GelMA/ NS nanocomposite hydrogels with tunable physiochemical and drug carrier properties could provide a favorable option for accelerating bone repair.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; GelMA; Nanosilicate; Dexamethasone; Nanocomposite hydrogels; Bone repair; OSTEOGENIC DIFFERENTIATION; SCAFFOLDS; DELIVERY; SILICA